E-156 Rescue stenting with self-expandable and balloon-mounted stents for acute large vessel stroke after failed mechanical thrombectomy presumable due to underlying intracranial atherosclerosis: systematic review. (23rd July 2022) - Sequeiros, J; Rodriguez-Calienes, A; Malaga, M; Moran-Marinos, C; Grados-Espinoza, P; Terry-Escalante, F; Quispe-Vicuña, C; Chavez, F; Javier-Murillo, N; Alva-Diaz, C; Krishnaiah, B; Inoa, V; et al.
Abstract : Introduction: Underlying intracranial atherosclerosis (ICAS) has been reported as one of the main causes of failure to revascularization after mechanical thrombectomy (MT) in acute large vessel ischemic stroke. Rescue therapy with permanent stenting has some favorable evidence from retrospective databases and prospective cohorts. Self-expandable (SES) and balloon-mounted stents (BMS) had been used as rescue therapy in this setting. Objective: To assess the benefit and safety at 90 days of acute rescue intracranial stenting in patients who failed mechanical thrombectomy, presumable due to underlying intracranial atherosclerosis with a subgroup analysis based on the type of stent used. Methods: A systematic review in accordance with PRISMA guidelines was conducted. Searches were conducted using the PubMed/Medline, Scopus, Embase, and Cochrane databases up to March 12, 2022, including randomized clinical trials (RCT) and observational studies describing 90 days outcomes in large vessel stroke who underwent MT with refractory occlusion presumable due to underlying ICAS, type of stent used was clearly described on the publication. Our primary outcome was functional independence, defined as modified Rankin Scale score (mRS): 0–2. Safety outcomes were 90 days mortality, symptomatic intracranial hemorrhage (sICH) and all ICH. We performed a meta-analysis using the random effect model, Freeman-Tukey double arcsine transformation was used to stabilize the proportion variances. Heterogeneity was evaluated using the I^2 and considered high if over 70%. Results: Seventeen studies (n=974) were included for systematic review. Fifteen studies included patients who received any stent (n=527), and eight studies did not used any stent (n=447). Thirteen studies used SES (n=465); two studies used BMS (n=62). Pooled estimate proportion of functional independence at 90 days among patients who received any stent was achieved in 50.1% (95% IC:41.1–59.1, I2:73.3%) and 25.0% (95%IC: 9.0–46.0, I2: 94.5%) in patients with no stent. Same outcome was present in 51.1% (95% IC:41.4–60.5, I2:73%) and 44.2% (95% IC:18.6–73.2, I2:55%) in patients with SES and BMS, respectively.Mortality at 90 days was 16.1% (95%IC:10.7–23.5, I2:63.1%) among patients who received any stent and 30.0% (95%IC:16.0–45.0, I2:89.3%) with no stent. Symptomatic intracranial hemorrhage (sICH) was 7.9% (95%IC: 5.6–11.1, I2:0%) among patients who received any stent, and 7.0% (95%IC: 2.0–13.0, I2:72.7%) with no stent. All ICH was present in 11.1% (95%IC:6.6–18.2, I2: 0%) and 18% (95%IC: 12.0–24.0) respectively. Conclusion: Our study shows decent functional independence in patients with acute large vessel stroke who received any rescue stenting after failed mechanical thrombectomy presumable due to underlying intracranial atherosclerosis. The subgroup of patients who received SES presented the higher estimated pooled proportion of functional independence. Mortality, symptomatic intracranial hemorrhage, and all ICH were comparable in all groups. The study is limited by high heterogenicity, and unavailability of studies that directly compared to best medical treatment or a specific type of stent. Rescue stenting should be directly compared with the best medical treatment for failed MT in a randomized trial. Disclosures: J. Sequeiros: None. A. Rodriguez-Calienes: None. M. Malaga: None. C. Moran-Marinos: None. P. Grados-Espinoza4: None. F. Terry-Escalante: None. C. Quispe-Vicuña: None. F. Chavez: None. N. Javier-Murillo: None. C. Alva-Diaz: None. B. Krishnaiah: None. V. Inoa: None. D. Hoit: None. A. Arthur: None. N. Goyal: None.